The Body across the Lifespan: On the Relation between Interoceptive Sensibility and High-Order Body Representations - Raimo, Simona (Brain Sci, 2021)
Background: Interoceptive information plays a pivotal role in building higher-order cognitive body representations (BR) that neuropsychological and neuroimaging evidence classifies as action-oriented (i.e., body schema) or non-action-oriented (i.e., visuo-spatial body map). This study aimed to explore the development of BR, considering the association with the interoceptive sensibility throughout the lifespan. Methods: Two hundred thirty-nine healthy participants divided into five age groups (7 to 8 years; 9 to 10 years; 18 to 40 years; 41 to 60 years; over 60 years) completed a self-report measure of interoceptive sensibility (the Self-Awareness Questionnaire; SAQ) and were given tasks assessing the two BR (action-oriented: hand laterality task; non-action-oriented: frontal body evocation task). Results: Both children (7–8 and 9–10 years) and older adults (over 60 years) performed worse than young (18–40 years) and middle-aged adults (41–60 years) in action- and non-action-oriented BR tasks. Moderation analyses showed that the SAQ score significantly moderated the relationship between age and action-oriented BR. Conclusions: The current results are consistent with inverted U-shaped developmental curves for action- and non-action-oriented BR. As an innovative aspect, the ability to mentally represent one’s own body parts in diverse states could be negatively affected by higher interoceptive sensibility levels in childhood and late adulthood.